2022
DOI: 10.21771/jrtppi.2022.v13.no2.p28-36
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic Analysis and Adsorption Isotherm of Chicken Egg Shells and Membranes Against Synthetic Dyes

Abstract: Textile industry waste at this time is enough to worry the community and the environment. The presence of synthetic dyes in water is hazardous, even in small concentrations. These synthetic dyes are derivatives of aromatic compounds such as benzene, toluene, and naphthalene, which are more resistant and stable than natural dyes. The adsorption method is used because it is easier to do, has no side effects, and does not require complicated and expensive equipment. In this study, the shells and membranes of disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, m is the weight of the adsorbent used (g). kF and n are constants that combine factors affecting adsorption, such as the capacity and intensity of adsorption [12].…”
Section: Determination Of Adsorption Isothermsmentioning
confidence: 99%
“…Meanwhile, m is the weight of the adsorbent used (g). kF and n are constants that combine factors affecting adsorption, such as the capacity and intensity of adsorption [12].…”
Section: Determination Of Adsorption Isothermsmentioning
confidence: 99%
“…Previous research results showed that the effectiveness of using natural adsorbents from chitosan and coffee grounds activated carbon in reducing cadmium concentrations in industrial wastewater was 90.86% with a final concentration of 0.07 mg/L (Nurhidayanti et al, 2021). Previously, the isotherm model and kinetics of arsenic metal in reducing arsenic metal (Nurhidayanti & Nugraha, 2022) , kinetic analysis and adsorption isotherm of chicken egg shells and membranes against synthetic dyes (Hevira & Gampito, 2022), kinetic analysis and adsorption isotherm of cadmium onto microalgae Parachlorella sp (Dirbaz & Roosta, 2018) had been studied . However, the proper lead metal adsorption isotherm model has not been studied to determine the adsorption capacity of the use of chitosan and coffee grounds adsorbents in reducing lead concentrations in industrial wastewater (Nurhidayanti et al, 2021; .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that the reduction of lead concentration in industrial wastewater using natural chitosan and activated carbon from coffee grounds as sorbents resulted in a reduction of 90.86%, yielding a final concentration of 0.09 mg/L (Nurhidayanti, Ilyas, & Suwazan, 2021). Previous research has explored the isothermal model and reaction kinetics of metallic arsenic reduction (Nurhidayanti & Nugraha, 2022), as well as the reaction kinetic analysis and adsorption isotherms of chicken egg shells, membranes, and synthetic dyes (Hevira & Gampito, 2022). However, the proper lead metal adsorption isotherm model has not been studied to determine the adsorption capacity of the use of chitosan and coffee grounds adsorbents in reducing lead concentrations in industrial wastewater (Nurhidayanti et al, 2021;Suwazan, Nurhidayanti, Fahmi, & Riyadi, 2022).…”
Section: Introductionmentioning
confidence: 99%